Realistic Mathematics Education (RME) Learning Model Improves Conceptual and Procedural Understanding of Junior High School Students - Sunyoto Hadi Prayitno; Wawan Gunawan; Feny Rita Fiantika; Hartono; Iis Holisin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Currently, there are still many students who feel they need to be more confident in studying mathematics. Most students are weak in conceptual understanding and procedural knowledge. This research aims to analyze the effect of the realistic mathematics education (RME) approach on students' conceptual and procedural understanding. The type of research used is a quasi-experiment (Quasi Experiment). The design of this research is a non-equivalent pot-test-only control group design. The population of this study was all class VII students, totaling 133 students. Sampling used a simple random sampling technique. The total sample is 58 students. The method used to collect data is a test. The instrument used to collect data is test questions. The techniques used to analyze data are descriptive statistical analysis and inferential statistics. The research results show differences between students who follow the realistic mathematics education (RME) learning model and students who do not follow the realistic mathematics education (RME) learning model regarding students' conceptual and procedural abilities. It was concluded that the realistic mathematics education (RME) learning model can improve conceptual and procedural abilities in junior high school students.